Sale of critically endangered sharks in the United States - Savannah J. Ryburn; Tammy Yu; Kelly J. Ong; Eldridge Wisely; Meggan A. Alston; Ella Howie; Peyton LeRoy; Sarah Elizabeth Giang; William Ball; Jewel Benton; Robert Calhoun; Isabella Favreau; et al. (Frontiers in Marine Science, 2025)
In the United States, shark meat is sold in grocery stores, seafood markets, and online. The meat is often mislabeled as another species or generically labeled as “shark”. The ambiguity of these generic labels makes it challenging to assess the conservation implications of this practice and for consumers to avoid high trophic-level species that often have high mercury concentrations in their tissues. We purchased and DNA barcoded 29 shark products in the United States to determine their species identity. Our samples consisted of 19 filets sold in grocery stores, seafood markets, and Asian specialty markets (mostly in North Carolina) and 10 ordered online as “jerky”. Ninety three percent of samples (27 of 29) were ambiguously labeled as shark or mako shark but not as a specific species. Of the two samples that were labeled to species, one was mislabeled (e.g., shortfin mako shark labeled as blacktip shark) and the other was correctly labeled. Barcoding indicated that the 29 samples included 11 different species of shark, including three species listed by the IUCN as Critically Endangered: great hammerhead, scalloped hammerhead, and tope. Previous studies have found that the first two species contain very high levels of mercury, illustrating the implications of seafood mislabeling for human health. The availability of shark meat in U.S. grocery stores is surprising given the dramatic decline of shark populations globally. Moreover, the fact that nearly all shark meat is labeled ambiguously or incorrectly amplifies the problem. Accurate, verified product labels for shark meat would benefit consumers and shark conservation efforts, and should be a priority for the seafood industry.

Utilization and outcomes of serial cervical cancer screening in a National Breast and Cervical Cancer Early Detection Program (NBCCEDP) in a non-Medicaid expansion state - Rubina Ratnaparkhi; Ahmed Ismail; Hope Krebill; Ian Cook; Melissa Javellana; Andrea Jewell; Lori Spoozak; Amanda Emerson; Megha Ramaswamy; Elizabeth Calhoun; Dinesh Pal Mudaranthakam (Cancer Causes & Control, 2025)

Parasite transmission stage abundance varies in lakes over time and space - Elizabeth S. Davenport; Marcin K. Dziuba; Logan E. Jacobson; Siobhan K. Calhoun; Kira J. Monell; Meghan A. Duffy (Limnology and Oceanography, 2024)
Environmentally transmitted parasites produce transmission stages that can remain viable and infective for extended periods of time in the environment where susceptible hosts may encounter them. Although many parasites have this mode of transmission, the abundance and distribution of environmental transmission stages have largely been overlooked, especially in aquatic habitats. Without empirical data to characterize spatial and temporal dynamics of parasite transmission stages in the environment, we might make incorrect assumptions about host–parasite contact rates. For aquatic environments, seasonal habitat structure driven by thermal stratification has been hypothesized to affect the patchiness of transmission stages within the water column, leading to uneven exposure risk to hosts. In this study, we quantified transmission stage concentrations of five common parasites of Daphnia spp. and Ceriodaphnia dubia at every meter of the water column at the deep basin of six lakes in southeastern Michigan every 2 weeks from June to November 2021. We found that transmission stage concentration varied by orders of magnitude over time and with depth. We investigated several possible drivers of these spatial and temporal patterns. For instance, our results suggest that greater mixing depth decreased transmission stage vertical patchiness within the water column of lakes with lower Fee's p values. However, horizontal spore patchiness across a lake was not correlated with the nearshore–offshore gradient of our study lakes. Overall, the results of our study show that parasite transmission stage concentrations have spatial and temporal dynamics that could affect disease dynamics within highly structured aquatic environments.

How does parasite environmental transmission stage concentration change before, during, and after disease outbreaks? - Elizabeth S. Davenport; Marcin K. Dziuba; Logan E. Jacobson; Siobhan K. Calhoun; Kira J. Monell; Meghan A. Duffy (Ecology, 2024)
Outbreaks of environmentally transmitted parasites require that susceptible hosts encounter transmission stages in the environment and become infected, but we also know that transmission stages can be in the environment without triggering disease outbreaks. One challenge in understanding the relationship between environmental transmission stages and disease outbreaks is that the distribution and abundance of transmission stages outside of their hosts have been difficult to quantify. Thus, we have limited data about how changes in transmission stage abundance influence disease dynamics; moreover, we do not know whether the relationship between transmission stages and outbreaks differs among parasite species. We used digital PCR to quantify the environmental transmission stages of five parasites in six lakes in southeastern Michigan every 2 weeks from June to November 2021. At the same time, we quantified infection prevalence in hosts and host density. Our study focused on eight zooplankton host species ( Daphnia spp. and Ceriodaphnia dubia ) and five of their parasites from diverse taxonomic groups (bacteria, yeast, microsporidia, and oomycete) with different infection mechanisms. We found that parasite transmission stage concentration increased prior to disease outbreaks for all parasites. However, parasites differed significantly in the relative timing of peaks in transmission stage concentration and infection outbreaks. The “continuous shedder” parasites had transmission stage peaks at the same time as or slightly after the outbreak peaks. In contrast, parasites relying on host death for transmission (“obligate killers”) had transmission stage peaks before outbreak peaks. For most parasites, lakes with outbreaks had higher spore concentrations than those without outbreaks, especially once an outbreak began; the exception was for a parasite, Pasteuria ramosa , with very strong genotypic specificity of infection. Overall, our results show that disease outbreaks are tightly linked to transmission stage concentration; outbreaks were preceded by increases in transmission stage concentration in the environment and then were fueled by the production of more transmission stages during the outbreak itself, with concentrations decreasing to pre‐outbreak levels as outbreaks waned. Thus, tracking transmission stages in the environment improves our understanding of the drivers of disease outbreaks and reveals how parasite traits may affect these dynamics.

Use of cervical cancer preventive services among US women aged 21–29: an assessment of the 2010 Affordable Care Act rollout through 2018 - Carlos O. Garrido; Rebekah A. Coşkun; Adrienne B. Lent; Elizabeth Calhoun; Robin B. Harris (Cancer Causes & Control, 2020)

TERRESTRIAL HABITAT SELECTION AND STRONG DENSITY‐DEPENDENT MORTALITY IN RECENTLY METAMORPHOSED AMPHIBIANS - David A. Patrick; Elizabeth B. Harper; Malcolm L. Hunter; Aram J. K. Calhoun (Ecology, 2008)
To predict the effects of terrestrial habitat change on amphibian populations, we need to know how amphibians respond to habitat heterogeneity, and whether habitat choice remains consistent throughout the life‐history cycle. We conducted four experiments to evaluate how the spatial distribution of juvenile wood frogs, Rana sylvatica (including both overall abundance and localized density), was influenced by habitat choice and habitat structure, and how this relationship changed with spatial scale and behavioral phase. The four experiments included (1) habitat manipulation on replicated 10‐ha landscapes surrounding breeding pools; (2) short‐term experiments with individual frogs emigrating through a manipulated landscape of 1 m wide hexagonal patches; and habitat manipulations in (3) small (4‐m 2 ); and (4) large (100‐m 2 ) enclosures with multiple individuals to compare behavior both during and following emigration. The spatial distribution of juvenile wood frogs following emigration resulted from differences in the scale at which juvenile amphibians responded to habitat heterogeneity during active vs. settled behavioral phases. During emigration, juvenile wood frogs responded to coarse‐scale variation in habitat (selection between 2.2‐ha forest treatments) but not to fine‐scale variation. After settling, however, animals showed habitat selection at much smaller scales (2–4 m 2 ). This resulted in high densities of animals in small patches of suitable habitat where they experienced rapid mortality. No evidence of density‐dependent habitat selection was seen, with juveniles typically choosing to remain at extremely high densities in high‐quality habitat, rather than occupying low‐quality habitat. These experiments demonstrate how prediction of the terrestrial distribution of juvenile amphibians requires understanding of the complex behavioral responses to habitat heterogeneity. Understanding these patterns is important, given that human alterations to amphibian habitats may generate extremely high densities of animals, resulting in high density‐dependent mortality.

Genetic diversity and population structure of Escherichia coli isolated from freshwater beaches - Seth T. Walk; Elizabeth W. Alm; Lisa M. Calhoun; Janice M. Mladonicky; Thomas S. Whittam (Environmental Microbiology, 2007)
Summary Escherichia coli is an important member of the gastrointestinal tract of humans and warm‐blooded animals (primary habitat). In the external environment outside the host (secondary habitat), it is often considered to be only a transient member of the microbiota found in water and soil, although recent evidence suggests that some strains can persist in temperate soils and freshwater beaches. Here we quantified the population genetic structure of E. coli from a longitudinal collection of environmental strains isolated from six freshwater beaches along Lake Huron and the St. Clair River in Michigan. Multilocus enzyme electrophoresis (MLEE) and multilocus sequence typing (MLST) revealed extensive genetic diversity among 185 E. coli isolates with an average of 40 alleles per locus. Despite evidence for extensive recombination generating new alleles and genotypic diversity, several genotypes marked by distinct MLEE and MLST profiles were repeatedly recovered from separate sites at different times. A PCR‐based phylogrouping technique showed that the persistent, naturalized E. coli belonged to the B1 group. These results support the hypothesis that persistent genotypes have an adaptive advantage in the secondary habitat outside the host.